Aesthetic Disinterestedness from a Metaphysical Point of View - Sílvia (Con-Textos Kantianos. International Journal of Philosophy, 2025)
What is the metaphysical significance of the aesthetic disinterestedness? In this paper, I address this question by examining the tension between aesthetic disinterest and intellectual—or metaphysical—interest in Kant’s Critique of the Power of Judgment. While aesthetic disinterestedness is often interpreted as a mark of the autonomy of the aesthetic sphere, I argue that this autonomy is deeply entangled with a reason’s aspiration towards systematic and metaphysical unity. Against the background of contemporary readings—particularly those of Dieter Henrich—I explore how the disinterested aesthetic attitude may serve as a starting point for a renewed engagement with the metaphysical dimension of Kant’s philosophy, offering a reinterpretation that resists ontologisation while highlighting the idealist orientation of Kant’s critical system.